Liquorpunktion – Schritt für Schritt - Siedler, Gabriela; Kallmünzer, Bernd; Schwab, Stefan (Deutsche Medizinische Wochenschrift, 2019)
Performing a diagnostic lumbar puncture is an essential clinical skill for the clinician. The procedure is of high importance for both, the emergency care for patients with suspected infection of the cerebral nervous system or subarachnoidal hemorrhage, as well as the elective diagnostic work up of chronic disease including multiple sclerosis and dementia. Furthermore the technique's principles are applied for spinal anesthesia or the intrathecal administration of drugs. This article describes a Standard Operating Procedure for the lumbar puncture step by step. Based on the latest evidence, it particularly focusses on clinically relevant questions and practical aspects.
CRIS-Team Scopus Importer:2019-10-08
Keywords: atraumatic needle; cerebrospinal fluid analysis; diagnostic lumbar puncture; post-lumbar; puncture headache